Critical analysis of prohibited activities for cooperatives of work in Argentina - Sosa, Gustavo Alberto (Cooperativismo & Desarrollo, 2019)
In 1994, the Argentine National Executive Power issued Decree 2015/94, by which it was established that at that time National Institute of Cooperative Action (inac), currently the National Institute of Associations and Economics Social (Inaes), should abstain from authorizing to work cooperatives that provide, in compliance of its social objective, to contract cooperative services by third persons employing the labor force of its associates In order to regulate said Decree, the inac issued Resolution No. 1510/94, by which it declared Under this situation, applications for authorization to operate as a work cooperative link with the following activities: placement agencies, cleaning, security, correspondence distributions and eventual services. In this way, an impediment to the development of new cooperatives was consecrated of a clearly illegitimate nature, since it was assumed, from the beginning, the activity in fraud to the labor law (and, as counterpart of the same currency, to the cooperative norm) before having the possibility to function the entities. The State thus renounced to exercise its supervisory role, by plainly and simply prohibiting the development of certain activities by worker cooperatives. Also, it was put under “mantle of suspicion” all cooperativized work activity that will develop outside of a trade or a manufacturing plant. However the time elapsed and the events that have taken place in the country since then, these prohibitions remain valid despite its manifest illegality.